Thermokinetic study of the isomerization of isocyanic acid - Tho, Nguyen Huu (Vietnam Journal of Chemistry, 2017)
In this work, the detailed study on the mechanism, kinetics and thermochemistry of the isomerization of isocyanic is described. Theoretical study was carried out by ab initio molecular orbital theory based on the CCSD(T) and B3LYP/6-311++G(3df,2p) methods in conjunction with statistical theoretical kinetic Rice-Ramsperger-Kassel-Marcus (RRKM) Master equation calculations. The potential energy surface (PES) for the isomeric reactions was also examined. At 760 Torr pressure, temperature dependent rate constants of the isomeric reactions HNCO ® HOCN (a), HNCO ® H(CNO) (b) and HNCO ® H(NCO) (c) were: k(T) (a) = 10-37.70.T13.09.e-93.30kcal/mol/RT, k(T) (b) = 103.46.T1.76.e-93.98kcal/mol/RT, k(T) (c) = 10-28.50.T10.61.e-91.16kcal/mol/RT respectively. Calculated results show that the isomerization of isocyanic acid may take place via three mechanisms and have very high barriers; all rate constants of them are very small in the temperature range from 300 to 2000 K. Keywords. Potential energy surface, isocyanic acid, density function theory, isomerization.